(Re)thinking teaching after COVID-19 school lockdown: a longitudinal study of Finnish primary school teachers’ expectations for, and perceptions of, change - Mankki, Ville (Routledge, Taylor & Francis Group, 2025)
Ever since COVID-19 forced schools to shift to distance teaching, there has been a wide range of speculations on how the period is going to shape the teaching in classrooms when the schools reopen. The current longitudinal study investigates Finnish primary teachers’ expectations and perceived outcomes concerning the change in teaching practices and attitudes. Twenty teachers were interviewed for the first time in April 2020 during the two-month national school lockdowns. The follow-up interviews were conducted a year later at the end of a school year with teaching organised as contact teaching. The findings were classified into three categories: (1) fulfilled expectations, (2) unfulfilled expectations and (3) unexpected outcomes. The findings offer valuable empirical insights complementing the envisioned changes associated with school reopening. By highlighting the discrepancy between expectations and outcomes, the study provides a contribution to the existing literature on the complexity of educational change.